Effect of the Drum Height on the Seismic Behaviour of a Free-Standing Multidrum Column - Ante Buzov; Jure Radnić; Nikola Grgić; Goran Baloević (Advances in Materials Science and Engineering)
The results of a shake-table study on the effect of the drum height on the seismic behaviour and bearing capacity of small-scale free-standing multidrum columns are presented. Columns of equal height with one, three, and six drums through their height were considered for the case of their self-weight only and for the case with an additional weight on the top of the column. The columns were exposed to a horizontal base acceleration of three accelerograms by successively increasing the maximum acceleration to their failure. The characteristic displacements and accelerations of the column were measured. It was concluded that an increase in the number of blocks in the column can significantly increase or decrease its ultimate bearing capacity, depending on the type of the applied accelerogram. It is expected that the experimental database can be useful in the validation of nonlinear numerical models for the dynamic analysis of multidrum columns.